PENGARUH PENGENDALIAN INTERNAL, KEPEMILIKAN KELUARGA, DAN KETIDAKPASTIAN LINGKUNGAN TERHADAP PENGHINDARAN PAJAK (Studi Empiris Pada Perusahaan Manufaktur Yang Terdaftar di Bursa Efek Indonesia Periode 2017-2019) - Shaffi Zahrotul Mawaddah; Darsono Darsono (Diponegoro Journal of Accounting, 2022)
This study aims to examine the effect of internal control, family ownership and environmental uncertainty on tax avoidance in manufacturing companies in Indonesia. Tax avoidance is one of the efforts made by the company to minimize the tax burden. Many factors that influence tax avoidance, including internal control, family ownership, and environmental uncertainty are used in this study because of the findings that are still mixed from previous studies.In this study, agency theory is used to formulate the three hypotheses that will lead to the results of the analysis. The three hypotheses in this study each want to show the direction of the positive or negative influence of each independent variable on the dependent variable. Technical analysis used in this research is multiple linear regression analysis.The population in this study were 507 observations on manufacturing companies listed on the IDX in 2017-2019. The sample in this study was selected using a purposive sampling method with certain criteria, and obtained as many as 219 observations on manufacturing companies that meet the criteria. The results of the analysis show that tax avoidance and environmental uncertainty have a negative effect, while family ownership has no effect on tax avoidance.